Synthesis of Highly-Dispersed Graphene Oxide Nanoribbons–Functionalized Carbon Nanotubes–Graphene Oxide (GNFG) Complex and Its Application in Enhancing the Mechanical Properties of Cementitious Composites - Li, Peiqi (Nanomaterials (Basel), 2021)
In this study, a graphene oxide nanoribbons–functionalized carbon nanotubes–graphene oxide (GNFG) complex was hydrothermally synthesized as a nanomaterial for reinforcing cementitious composites, using a modified Hummers’ method. Three types of components existed in the GNFG: Type I, the functionalized carbon nanotubes–graphene oxide nanoribbons (FCNTs–GNR); and types II and III are graphene oxide (GO) and functionalized carbon nanotubes (FCNTs), respectively, which exist independently. The dispersivity of GNFG and its effects on the mechanical properties, hydration process, and microstructures of cement pastes were evaluated, and the results were compared with those using cement pastes incorporating other typical carbon nanomaterials. The results demonstrated that dispersion of GNFG in aqueous solutions was superior to that of the CNTs, FCNTs, and GO/FCNTs mixture. Furthermore, the highly-dispersed GNFG (0.05 wt.%) improved the mechanical properties of the cement paste after 28 days of hydration and promoted the hydration of cement compared to CNTs, GO, and GO/FCNTs mixture (0.05 wt.%). The results in this study validated the feasibility of using GNFG with enhanced dispersion as a new nano-reinforcing agent for various cementitious systems.